Peran Pendidikan Ekonomi pada Pengrajin Dupa Ratus - Achmad Maulana Adyaksa; Hari Wahyono; Cipto Wardoyo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The hundred incense craftsmen in the village of Dalisodo initially had jobs as farmers and ranchers until finally they chose to become hundred craftsmen of incense. The existence of hundred incense craftsmen in the Dalisodo village is very influential on the development of the Dalisodo village especially in the Malang Regency because they are able to produce high quality products and the products are marketed all the way to Bali Island. The method of this research uses qualitative. With this type of approach to femenology. And in determining subjects using puposive sampling. In carrying out every activity, the hundred incense craftsmen possess the role of economic education, including from the family, craftsmen, laborers, and in the hundred incense production process.Abstrak: Pengrajin dupa ratus di Desa Dalisodo pada awalnya memiliki pekerjaan sebagai petani dan peternak hingga akhirnya mereka memilih menjadi pengrajin dupa ratus. Keberadaan pengrajin dupa ratus  di desa Dalisodo sangat berpengaruh  terhadap perkembangan di desa Dalisodo, khusunya di wilayah Kabupaten Malang karena mereka mampu memproduksi dengan produk yang sangat berkualitas dan hasil produksi di pasarkan hingga ke Pulau Bali. Metode penelitian ini menggunakan kualitatif dengan jenis pendekatan fenomenologi dan dalam menentukan subyek menggunakan puposive sampling. Di dalam melakukan setiap kegiatannya, pengrajin dupa ratus memiliki peran pendidikan ekonomi, meliputi dari dalam keluarga, pengrajin, buruh kerja, dan di dalam proses produksi dupa ratus.